2021
DOI: 10.3389/fmed.2021.776876
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Chloride Sensitizes Cisplatin Resistance of Ovarian Cancer Cells via PI3K/Akt Pathway

Abstract: Our previous study manifested that lanthanum chloride (LaCl3) can enhance the anticancer ability of cisplatin (DDP) in ovarian cancer cells. Here, ovarian cancer cells SKOV3 and SKOV3/DDP were subjected to DDP and LaCl3. Cell viability, apoptosis, DNA repair, and PI3K/Akt pathway were detected. LaCl3 induced more cell death and apoptosis caused by DDP in two cell lines, accompanied by upregulation of Bax and Cleaved caspase 3 proteins, and downregulation of Bcl-2 protein. LaCl3 also could decrease RAD51 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One of the possible mechanism underlining this is P13K/Akt/mTOR pathway; a major signal transduction cascade hyper-activated in most cancers whose activation leads to cancer cells survival and its proliferation via attenuating the antitumor effect of chemotherapeutics, 52,53 performs a crucial part in cancer cells CDDP resistance and ultimately reduces its antitumor efficiency. 54 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the possible mechanism underlining this is P13K/Akt/mTOR pathway; a major signal transduction cascade hyper-activated in most cancers whose activation leads to cancer cells survival and its proliferation via attenuating the antitumor effect of chemotherapeutics, 52,53 performs a crucial part in cancer cells CDDP resistance and ultimately reduces its antitumor efficiency. 54 …”
Section: Resultsmentioning
confidence: 99%
“…† 27 One of the possible mechanism underlining this is P13K/ Akt/mTOR pathway; a major signal transduction cascade hyper-activated in most cancers whose activation leads to cancer cells survival and its proliferation via attenuating the antitumor effect of chemotherapeutics, 52,53 performs a crucial part in cancer cells CDDP resistance and ultimately reduces its antitumor efficiency. 54 OA enhanced the apoptosis for CDDP/OA-LCC NPs against the HCC via Bad over expression by suppressing the AMPK/ P13K/Akt/mTOR pathway activation 55 synthesis in cancer cells, and, by phosphorylating its upstream inhibitory regulator, TSC2 and Raptor; its regulatory subunit.…”
Section: In Vivo Antitumor Efficacy and Tunel Assaymentioning
confidence: 98%
“…A synergistic effect of LaCl 3 on cisplatin-induced inhibition of ovarian cancer cell proliferation and tumor growth has been found ( 18 , 19 ). The application of La 2 O 3 nanoparticles can also improve the therapeutic benefits of radiation therapy and chemotherapy with temozolomide in the treatment of glioblastoma ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have indicated that La has an anti-cancer effect on several cervical cancer cells, hepatocellular carcinoma cells, and ovarian cancer cells ( 15 19 ). Other studies, however, showed that La has carcinogenic potential when its concentration fluctuates in colorectal and hepatic cancer cells ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Imperatorin is a furanocoumarin compound extracted from the traditional Chinese medicine angelica, which has inhibitory effects on cisplatin-resistant cervical cancer Hela/R cells. It can upregulate the Bim protein and release cytochrome c (CytC) and activate caspase 3, thereby increasing the sensitivity of HeLa/R to cisplatin [ 179 ]. Metformin can upregulate the expression of Bax and decrease the expression of Bcl-2 and the mRNA level of AKT1, thereby inhibiting the viability and inducing the apoptosis of the Ishikawa/DDP cell line [ 180 ].…”
Section: Potential Mechanisms Of Plant-derived Natural Products In Th...mentioning
confidence: 99%